Transition‐Metal‐Catalyzed Laboratory‐Scale Carbon–Carbon Bond‐Forming Reactions of Ethylene. Issue 43 (17th September 2013) - Saini, Vaneet; Stokes, Benjamin J.; Sigman, Matthew S.
Abstract Ethylene, the simplest alkene, is the most abundantly synthesized organic molecule by volume. It is readily incorporated into transition‐metal‐catalyzed carbon–carbon bond‐forming reactions through migratory insertions into alkylmetal intermediates. Because of its D2h symmetry, only one insertion outcome is possible. This limits byproduct formation and greatly simplifies analysis. As described within this Minireview, many carbon–carbon bond‐forming reactions incorporate a molecule (or more) of ethylene at ambient pressure and temperature. In many cases, a useful substituted alkene is incorporated into the product.